Computational design and investigation of the monomeric spike SARS-CoV-2-ferritin nanocage vaccine stability and interactions - Garmeh Motlagh, Farnaz; Azimzadeh Irani, Maryam; Masoomi Nomandan, Seyedeh Zeinab; Assadizadeh, Mohammad (Frontiers in Molecular Biosciences, 2024)
Since the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) outbreak, several solutions have been proposed to manage the disease. The most viable option for controlling this virus is to produce effective vaccines. Most of the current SARS-CoV-2 vaccines have focused on the infusion spike protein. Spike exists as a trimer and plays a vital role in infecting host cells by binding to the Angiotensin-Converting Enzyme 2 (ACE2) receptor through its Receptor Binding Domain (RBD). Ferritin protein, a naturally occurring iron-storage protein, has gained attention for vaccine production due to its self-assembling property, non-toxic nature, and biocompatibility. Ferritin nanocages have recently been employed in the development of a SARS-CoV-2 vaccination eliciting not only long-term protective memory cells but also a sustained antibody response. In this study, a combination of in silico investigations including molecular docking, molecular dynamics simulations, and immune simulations were carried out to computationally model the monomeric spike protein on the ferritin nanocage as well as to evaluate its stability and interactions for the first time. The structural dynamics of the modeled complex demonstrated noticeable stability. In particular, the Receptor Binding Domain (RBD) and ferritin within the monomeric spike-ferritin complex illustrated significant stability. The lack of alterations in the secondary structure further supported the overall steadiness of the complex. The decline in the distance between ferritin and spike suggests a strong interaction over time. The cross-correlation matrices revealed that the monomeric spike and ferritin move towards each other supporting the stable interaction between spike and ferritin. Further, the orientation of monomeric spike protein within the ferritin unit facilitated the exposure of critical epitopes, specifically upward active Receptor Binding Domain (RBD), enabling effective interactions with the ACE2 receptor. The immune simulations of the model indicated high-level stimulations of both cellular and humoral immunity in the human body. It was also found that the employed model is effective regardless of the mutated spikes in different variants. These findings shed light on the current status of the SARS-CoV-2-ferritin nanoparticle vaccines and could be used as a framework for other similar vaccine designs.